Chad : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2007)
This Selected Issues paper aims at discussing the impact of the oil windfall on Chad, with a focus on growth, poverty, competitiveness, and fiscal policy challenges posed by the oil revenue outlook. The paper discusses the reforms needed to remove structural factors that constraints the non-oil sector growth, in particular on civil and military services and the microfinance sector. The paper argues that Chad's current growth potential is seriously limited by low levels of both human and physical capitals and by weak institutions and governance.